Towards a Systemic Social Medicine: Epistemological Foundations and Operational Perspectives (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
In recent years, renewed attention has been devoted to the epistemological and operational foundations of Social Medicine. Building on contributions to Global Social Medicine and critical analyses of the political economy of healthcare, this article advances the notion of Systemic Social Medicine. Grounded in complexity theory and systemic epistemology, this framework transcends reductionist paradigms and repositions health as an emergent property of interrelated biological, social, and political determinants. Four epistemic axes are proposed relationality, conscious and cooperative reduction, transcendence of knowledge, and global relationality aiming to reconfigure both clinical reasoning and public health practice within a genuinely systemic perspective.
Keywords: systemic social medicine; epistemology of complexity; relationality; global health; evidence-based medicine